ANALISIS MANAJEMEN MUTU PELAYANAN KESEHATAN PADA RUMAH SAKIT - Maesstro Bina Utama Simanjuntak (Majalah Ilmiah METHODA, 2018)
The basic nature of the hospital is the fulfillment of the needs and demands of patients who expect to resolve their health problems in hospitals because they are considered hospitals capable of providing medical services as an effort to cure and restore pain and patients expect services that are ready, fast, responsive and comfortable with complaints. Patient satisfaction can be influenced by the quality of health services provided by the hospital to the provider, where the quality of health services for patients means empathy, respect and responsiveness to their needs. Therefore the quality of health services at the hospital is important because it is seen from the reciprocity that will be obtained by the hospital itself.